Measuring Work Related Physical and Mental Health Function: Updating the Work Disability Functional Assessment Battery (WD-FAB) Using Item Response Theory. Issue 3 (March 2019) - Marfeo, Elizabeth E.; McDonough, Christine; Ni, Pengsheng; Peterik, Kara; Porcino, Julia; Meterko, Mark; Rasch, Elizabeth; Kazis, Lewis; Chan, Leighton
Abstract : Objective: To further improve measurement of work-related physical and mental health by updating the Work Disability Assessment Battery (WD-FAB). Methods: Cross-sectional study with 1024 disability claimants and 1000 working age (21 to 66 years) adults in the United States. Developed new items to replenish the WD-FAB and analyzed using factor analysis and item response theory (IRT). Computer adaptive testing (CAT) simulations evaluated the psychometric properties of the original versus updated WD-FAB. Results: Analyses confirmed the structure of the WD-FAB. Twenty-three new items were added (basic mobility: 7, upper body function: 4, fine motor: 6, self-regulation: 1, resilience & sociability: 5 items). Conclusions: Findings support the WD-FAB as a robust, psychometrically sound assessment of work-related function. Extensive content coverage (331 items) represents eight physical and mental health domains. IRT/CAT methods allow administration in under 15 minutes. The WD-FAB may prove valuable for efficiently characterizing work-related function across work rehabilitation settings.